RESOURCES OF FISH IN BOTTOM BIOTOPES ON THE SHELF AND THE UPPER CONTINENTAL SLOPE IN THE NORTHWESTERN BERING SEA - A. B. Savin (Известия ТИНРО, 2018)
Stock of demersal fish species at the depths of 20–386 m in the northwestern Bering Sea, as well as pelagic and anadromous fishes in the bottom biotopes, are considered on the data of the bottom trawl survey conducted within the West-Bering and Chukchi fishery districts in the summer of 2017. The total accounted biomass of demersal fish was 1756,870 t, including 1578,430 t in the West-Bering and 178,440 t in the Chukchi district. The mean distribution density was similar in both districts: 11331.8 and 10748.0 kg/km2, respectively. Pacific cod formed the bulk of the demersal fish biomass — 1227,300 t.  Among other species, the stocks were considerable for flathead sole — 96,310 t, great sculpin — 79,160 t, alaska plaice — 71,200 t, and arrowtooth flounder — 40,630 t, and the summary biomass of all others was 242,270 t. The total biomass of pelagic and anadromous fish species presented in the bottom biotopes was estimated as 3884,150 t, including 3555,930 t in the West-Bering and 328,220 t in the Chukchi district. They had higher distribution density in the West-Bering district — 25527.9 kg/km2 vs 19769.9 kg/km2 in the Chukchi district. Walleye pollock prevailed among these species with the total biomass 3884,150 t (assessed with the catchability coefficient for adults k = 0.4), including 36,080 t of accounted yearlings (k = 0.1). Biomasses of other pelagic fishes in the bottom biotopes were 415,380 t for pacific herring, 18,680 t for arctic cod, 920 t for capelin, and 260 t for all others in sum. Comparing these new assessments with the data of analogous survey in 2015, the stocks of pacific herring, rock sole, alaska plaice, and ray Bathyraja parmifera have decreased and the stocks of arctic cod, saffron cod, pacific cod, walleye pollock (both adults and yearlings), flathead sole, and yellowfin sole have increased. Positive and negative anomalies from the standard curves of size composition for some species could be considered as a basement for forecasting of their stocks tendencies in the nearest future.